The Impact of Family Status on the Enforcement of Gratification Laws in Indonesia - Sariat Arifia; Bambang Aref Wibowo; Caskiman (Humanities, Society, and Community, 2025)
This research examined the influence of family status on enforcing anti-gratification laws in Indonesia. This study aimed to identify how familial relationships affect legal processes, identify legal loopholes, and offer recommendations to enhance anti-gratification enforcement. The research analyzed recent cases involving high-ranking officials using a normative and descriptive-analytical approach. This study focused on the legal significance of family information recorded on the official Family Card (Kartu Keluarga) and its impact on case identification and prosecution. Findings revealed that family status played a significant role in tracking asset flows and establishing links between public officials and gratification sources. However, ambiguities in the legal definition of "family" often created loopholes that obstructed consistent legal action. The study also found that social media had become an unintentional yet powerful channel for exposing gratification cases, particularly through content shared by family members. While such public disclosures prompted official investigations, they also raised concerns about objectivity and legal consistency. The research concluded that comprehensive legal reform is essential to clarify familial definitions, close enforcement gaps, and ensure that digital disclosures are handled fairly. These findings strengthen Indonesia's legal framework for combating corruption-related gratification practices.